PERBAIKAN BERKESINAMBUNGAN TERHADAP SISTEM PENELUSURAN MATERIAL DI PT XYZ - Ayu, Ketut Gita; Septivani, Nike; Cahyadi, Randy; Oktavia, Hellen; Juanda, Fandy (Industrial and Systems Engineering Assessment Journal (INASEA), 2013)
PT XYZ is engaged in the stamping and welding that produces various kinds of high-quality parts. There is a mismatch between the amount of material released with production, while the material tracking system applied does not provide clear information about the flow of material issued for production processes. This led to the use of the material becomes less effective. Material tracking system used is form called identity tag. This study aims to: (1) determine the influencing factors of problems on the amount of material work in process both planned and actual, (2) determine what types of most frequent problematic products on the amount of material work process, (3) determine an appropriate and effective system for PT XYZ in implementing manufacturing processes, (4) optimize the use of raw materials produced. Methods to solve the above problem are plan, do, check, action (PDCA) assisted with tools such as histograms, Pareto charts, cause-effect diagrams and kuesione. The result obtained and taken into consideration is giving improvement suggestions, which are doing more inspections by the production leader to reduce the error information written on the identity tag, and providing some additional columns, such as description and causes of the reduce in the amount of material that most often occurs. Based on the implementation results, the discrepancy percentage in the identity tag proposals decreases to 45.45% for small part, 53.33%, for medium part and 12.5% for large part, with a total percentage of 37.74% in week 1.